PEMANFAATAN BUTON GRANULAR ASPHALT TIPE B 5/20 PADA CAMPURAN ASPAL BETON TERHADAP NILAI KEAUSAN (CANTABRO TEST) - Wan Muhammad Iqbal; Winayati; Alfian Saleh (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2023)
Buton Granular Asphalt has properties to improve pavement characteristics because the material from Buton Granular Asphalt contains fine grains of material that provide strength to the road pavement so that with the increase in the strength of this pavement layer, it will affect the wear of the pavement due to the frictional force of the wheels on the road pavement. So it is necessary to do the properties and characteristics of the strength of the asphalt concrete mixture with the use of Buton Granular Asphalt. This research uses Buton Granular Asphalt as an added material for Asphalt Concrete – Wearing Course (AC-WC) pavement layers. The method used in this research is an experimental study in the laboratory by looking at the parameters and national standards set in laboratory testing. Buton Granular Asphalt is an asbuton product that has bitumen content between 20-25%. From the results of the Optimum Asphalt Content (KAO) test, the optimum asphalt content value is 5.64%. After getting the Optimum Asphalt Content, the test object was made with the addition of Buton Granular Asphalt, variations were made with values of 0%, 1%, 2%, and 3% of the asphalt weight. After making the test object, the cantabro test was carried out. From the results of the study, the value of weight loss at 0% levels was 8.82%, 1% levels were 5.18%, 2% levels were 2.46% and 3% levels were 1.84%. The results of this study indicate that the use of Buton Granular Asphalt material with a content of 3% has the lowest weight loss value, with the use of Buton Granular Asphalt as an added material has a high resistance to wear and tear. This indicates that adding Buton Granular Asphalt can make the pavement resistant to wear and tear caused by vehicle wheel friction and because the content of Buton Granular Asphalt consists of a fine material that can make the interlocking of the pavement mixture stronger.